2017
DOI: 10.1080/00221686.2016.1260656
|View full text |Cite
|
Sign up to set email alerts
|

Momentum balance in flows over mobile granular beds: application of double-averaging methodology to DNS data

Abstract: This paper presents the application of the double-averaging methodology to actual data obtained for the mobile-bed conditions from direct numerical simulations using an immersed boundary method. The dimensions of the computational domain resemble those for open-channel flows with small relative submergence. The domain bottom is a plane covered with one layer of hexagonally packed, single-size spheres fixed to the bed. The fixed particles are covered by 2000 mobile particles of the same size that are free to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…After an initialization period of 40T b (case HP) and 20T b (case LP) to reach steady-state conditions, the simulations were run for the total simulation time of 175 T b (case HP) and 134 T b (case LP), where T b = U b /H is the bulk time unit. Preliminary analysis showed that the generated data are sufficient for obtaining fairly converged first and second-order statistics in the major part of the simulation domain (Vowinckel, Nikora, et al, 2017). In the following, a summary of the key flow features of the two scenarios are given recapping the preliminary analyses presented in and .…”
Section: Key Parametersmentioning
confidence: 96%
See 2 more Smart Citations
“…After an initialization period of 40T b (case HP) and 20T b (case LP) to reach steady-state conditions, the simulations were run for the total simulation time of 175 T b (case HP) and 134 T b (case LP), where T b = U b /H is the bulk time unit. Preliminary analysis showed that the generated data are sufficient for obtaining fairly converged first and second-order statistics in the major part of the simulation domain (Vowinckel, Nikora, et al, 2017). In the following, a summary of the key flow features of the two scenarios are given recapping the preliminary analyses presented in and .…”
Section: Key Parametersmentioning
confidence: 96%
“…Application of this methodology for mobile-bed conditions, however, remains challenging as it requires highresolution data in both space and time. In a companion paper (Vowinckel, Nikora, Kempe, & Fröhlich, 2017), the DAM was successfully applied to DNS data in the analysis of the momentum balance in a turbulent flow over a mobile granular bed. Vowinckel, Nikora, et al (2017) provide details on the spacetime sampling and averaging strategies and report a detailed assessment of the key terms of the double-averaged momentum balance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all of the simulations to be presented in the following, we have chosen e dry = 0.97 and µ = 0.15, which is a common parameterization for silicate materials (e.g. Biegert et al 2017a;Joseph et al 2001;Joseph & Hunt 2004;Vowinckel et al 2014Vowinckel et al , 2017a.…”
Section: Cohesionless Particle-particle Interactionmentioning
confidence: 99%
“…Since the Gibson theory was derived for pure muds in the first place, applying the model to sand-mud mixtures might be problematic [38]. At the same time, the larger sized particles render the physical configuration attractive for phase-resolved simulations that allow for a full description of the fluid and the particle motion [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%